Investigation of laser-induced contamination on dielectric thin films in MHz sub-ps regime - Stehlik, Marek; Zideluns, Janis; Petite, Camille; Allard, Valentin; Minissale, Marco; Moreau, Antonin; Lereu, Aude; Lemarchand, Fabien; Wagner, Frank; Lumeau, Julien; Gallais, Laurent (Advanced Optical Technologies, 2024)
High-repetition rate diode-pumped sub-ps lasers are widely used in the industrial sector for highquality material processing applications. However, for their reliable operation, it is crucial to study the power handling capabilities of the optical components used in these systems. The optical components, such as mirrors, gratings, dichroic filters, and gain media, are designed based on dielectric thin films. When subjected to high-intensity laser radiation, the phenomenon of laser-induced contamination (LIC) can lead to the growth of a nanometric, highly absorbent layer on an irradiated optical surface, which can result in transmission or reflection loss and eventual permanent damage. In this study, we investigate LIC growth on dielectric oxide thin films in an air environment irradiated by MHz sub-ps laser at 515 nm. We examine the effect of thin film deposition method, material, and thickness on LIC growth dynamics. The irradiated spots on the surface are inspected using multiple observation methods, including white light interference microscopy and fluorescence imaging. Our results show that the LIC growth dynamics depend on the laser intensity and irradiation time and can be affected by the thin film deposition method, material, and thickness. These findings could be used to inform the development of more resistant optical components, ensuring long-term reliable laser operation required for industrial applications. The study highlights the need for validating optical components using tests that closely mimic real-world applications and provides insight into the complex processes that lead to LIC.